Assessing Knowledge, Attitude, Potential Barriers and Analysis of Motivational Factors of Blood Donation among Young Adults in an Endemic Area of Hemoglobinopathies in Saudi Arabia - Dobie, Gasim; Alfaifi, Bashayer Ahmed; Fageehy, Nameer Ali; Alhaqawe, Fatimah Mabrook; Essawi, Khaled; Hakami, Waleed; Chandika, Rama Mohan; Saboor, Muhammad; Madkhali, Aymen; Mobarki, Abdullah Ahmed; Madkhali, Maymoon Mohammed; Hamali, Hassan Abdu (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Blood and blood products are indispensable, lifesaving and essential in all components of healthcare systems globally. Blood (and blood product) transfusion is crucial for both routine and emergency medical practices. The adequacy of blood products is based on a sophisticated strategy for attracting and retaining donors, which is significantly influenced by the motivations that drive them. The success of Saudi Arabia's blood services may rely on understanding the motivational factors and potential barriers to donation among young adults. Materials and Methods: A cross-sectional descriptive study, with 773 participants of both genders, was conducted among young adults at Jazan University and Gizan City, Jazan region. The participants were asked to rate the significance of motivational factors and potential barriers that might affect their decision to donate blood in the future through a self-administered questionnaire. Results: The current study reported a notably low blood donation rate among young adults in Jazan region. The key potential barriers to the low blood donation rate were attributed to time constraints and being medically unfitness, with more than one-third of participants reporting being unqualified/medically unfit. Conversely, the study revealed the primary motivators for blood donation as a sense of duty, religious beliefs and altruism. Furthermore, factor analysis approaches indicated a three-factor solution for blood donor motivation, explaining a total of 75.50% of the variance: understanding factors (31.41%), enhancement and value factors (23.29%) and socio-demographic factors (20.78%). Notably, young men exhibited a higher attitude toward blood donation than young women, despite being outnumbered in the sample. Conclusion: The findings revealed a low donation rate due to identified potential barriers such as time constraints and medical eligibility, which need targeted intervention to improve blood donation rates among study participants. Implementing strategies that influence motivational factors, particularly among females, could enhance donor recruitment. The study provides empirical evidence for the necessity of the Voluntary Functions Inventory (VFI) within Saudi Arabian society and highlights the mandatory need for comprehensive education and awareness programs that address all aspects of blood donation.
Keywords: Blood; Donation; Voluntary Functions Inventory (VFI); Motivation; Barriers; Factor analysis; Knowledge; Awareness